A Review of Enzyme-Induced Calcium Carbonate Precipitation Applicability in the Oil and Gas Industry - Alarifi, Sulaiman A.; Mustafa, Ayyaz; Omarov, Kamal; Baig, Abdul Rehman; Tariq, Zeeshan; Mahmoud, Mohamed (Frontiers in Bioengineering and Biotechnology, 2022)
Enzyme-induced calcium carbonate precipitation (EICP) techniques are used in several disciplines and for a wide range of applications. In the oil and gas industry, EICP is a relatively new technique and is actively used for enhanced oil recovery applications, removal of undesired chemicals and generating desired chemicals in-situ, plugging of fractures, lost circulation and sand consolidation. Many oil- and gas-bearing formations encounter the problem of the flow of sand grains into the wellbore along with the reservoir fluids. This study offers a detailed review of sand consolidation using EICP to solve and prevent the sand production issues in oil and gas wells. Interest in bio-cementation techniques has gained a sharp increase recently due to its sustainable and environmentally friendly nature. An overview of the factors affecting the EICP technique are discussed with an emphasis on the in-situ reactions leading to sand consolidation. Furthermore, this study provides a guideline to assess sand consolidation performance and the applicability of EICP to mitigate sand production issues in oil and gas wells.